Blast and impact loading effects on glass and steel elements and materials. (January 2019) - Seica, Michael V.; Packer, Jeffrey A.; Yankelevsky, David Z.
Abstract: A review of recent research performed by the University of Toronto on blast and impact loading of structures in the last few years is presented. The structural elements and materials considered are: cold-formed square hollow structural sections (HSS), composite concrete-filled HSS, composite double-skin HSS, architectural glazing (annealed soda lime glass) and multi-layered laminated glazing panels, as well as energy-dissipating steel connectors. The research methodologies employed are: very large-scale arena testing by far-field air blasts, full-scale laboratory testing (including the use of a servo-hydraulic 'blast generator'), small-scale material dynamic testing (including the use of Split Hopkinson Pressure Bar apparatus), analysis using single degree of freedom (SDOF) models, and analysis using explicit (dynamic) finite element programs (including both in-house, purpose-written software and commercial programs such as LS-DYNA). Insights into high-strain-rate material behaviour and its modelling have been gained and used in comparing numerical models against test results. Highlights: Monolithic and laminated, annealed and heat-strengthened, glazing tested under blast loads. Hollow, concrete-filled and double-skin square hollow sections tested under blast loads. Large quantities of various explosives used in arena field tests: ANFO, TNT, Nitromethane. Instrumentation: conductive break circuits, non-contact gauges, high-speed data acquisition. Single Degree of Freedom and dynamic, non-linear, explicit finite element modelling.